Performance improvement of PV solar system by diffused reflection - Antu, Antara Debnath; Sarkar, Md. Robiul Islam; Alam, Naser Md. Isteaque (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.